Long-term research reveals potential role of hybrids in climate-change adaptation. A commentary on 'Expansion of the rare Eucalyptus risdonii under climate change through hybridisation with a closely related species despite hybrid inferiority'. (21st July 2021) - Bush, David
Abstract : This article comments on: T. R. Pfeilsticker, R. C. Jones, D. A. Steane, P. A. Harrison, R. E. Vaillancourt and B. M. Potts, Expansion of the rare Eucalyptus risdonii under climate change through hybridization with a closely related species despite hybrid inferiority, Annals of Botany, Volume 129, Issue 1, 1 January 2022, Pages 1–14 https://doi.org/10.1093/aob/mcab103